Le Château de Gaillon : un passé carcéral volontairement oublié - France Poulain (In Situ)
The castle of Gaillon has had several periods of occupation, the first under King Philippe Auguste of which only a few remains rest buried in the basement. A second during the Renaissance of which only a few major architectural elements remain such as the Entrance Pavilion and the Genoa Gate. The third period was in 1812 with the establishment of a central prison, one of the largest in Normandy. This period saw the reconstruction of 80% of the buildings sold off as National Goods after the French Revolution. Many families in the region found work at the prison as caretakers and washerwomen and local industries benefited from a source of cheap labor. However in the 19th century the prison started a long decline. The history of this period, is badly documented because the local population have tried to forget its reactivation as a prison during the Second World War, and instead the focus was turned to magnify the Renaissance period. The work carried out by Dominique Pitte and France Poulain on the castle consisted in carrying out an inventory of all the graffiti, traces and decorations still visible. This made it possible to reveal this recent history and to put it in perspective with history in general. Better understood, the graffiti is better preserved today. A space dedicated to this local history is being finalized in the castle.